Дослідження та програмна реалізація системи хмарного сервісу забезпечення безпеки розумного будинку - Мукієнко, Анатолій Андрійович; Mukienko, Anatolii (ЦНТУ, 2025)
В даній випускній кваліфікаційній роботі за другим (магістерським) рівнем вищої освіти розроблено програмне забезпечення, яке призначено для системи хмарного сервісу забезпечення безпеки розумного будинку. Метою розробки є дослідження та програмна реалізація системи хмарного сервісу забезпечення безпеки розумного будинку. Об’єктом дослідження є процес хмарного сервісу забезпечення безпеки розумного будинку. Предметом дослідження є методи хмарного сервісу забезпечення безпеки розумного будинку. In this final qualification work for the second (master's) level of higher education, software has been developed, which is intended for the cloud service system for ensuring the security of a smart home. The purpose of the development is the research and software implementation of the cloud service system for ensuring the security of a smart home. The object of the research is the process of the cloud service for ensuring the security of a smart home. The subject of the research is the methods of the cloud service for ensuring the security of a smart home.
Research and software implementation of the cloud service system for ensuring the security of a smart home
Keywords: комп’ютерні науки; хмарний сервіс; безпека; розумний будинок; computer science; cloud service; security; smart home